Gastrointestinal stromal tumor (GIST) as a cause of hemoperitoneum in a patient on peritoneal dialysis - Porta, Iliana (2023)
Introduction: Hemoperitoneum (PH) in peritoneal dialysis (PD) is rare, the most described cause is related to menstruation or catheter trauma. Case: A 56-years-old female patient with chronic kidney disease, two years on PD, presented abdominal pain during peritoneal fluid infusion and evidence of bloody drainage, empiric antibiotic therapy was started due to suspected peritonitis; she had surgery for exploratory laparotomy due to unfavorable clinical course. There was evidence of a bleeding tumor dependent on the back of the stomach, which was resected. Biopsy: benign gastrointestinal stromal tumor (GIST) of the stomach, spindle cell subtype. The patient had an unfavorable post-surgical evolution, persistence of bleeding, and deterioration of the clinical state, dying three weeks later. Conclusion: GIST should be considered in the differential diagnosis of hemoperitoneum in patients on peritoneal dialysis.